القواعد والضوابط الفقهية في المعاملات المالية المحرمة المتعلقة بالربا والغرر وتطبيقاتها في المصارف الإسلامية الماليزية - Zainudin bin Ismail (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2013)
This study focuses on the jurisprudential rules and regulations relating to the prohibited financial transactions, especially with regard to riba and gharar in their application to Malaysian Islamic banking transactions. This study adopts the analytical deductive approach which is executed by collecting, studying and analyzing these rules and regulations, and tracing them to their sources. The opinions of scholars, especially from the four schools of law in understanding the rules and their applications will also be covered. The researcher has referred to books Arabic and other languages. As for the application of these rules and regulations to contemporary Islamic banking transactions and discovering the truth about what is happening in this area, interviews have been conducted with specialists in this field. The researcher has collected elements relating to the prohibited financial transactions as they are excluded from the general rules: "Originally in transactions, they are permitted" These rules were identified first; then the rules and regulations relating to the forbidden financial transactions were collected. Since these rules and regulations are countless, the researcher has focused on two of these elements only, which are riba and gharar since they are categorized as the most important elements that lead to the prohibitions of financial transactions. These rules and regulations are gathered and explained in their sources, meanings and applications. If there are differences among jurists, their opinions, evidence and discussions will be stated and the strongest opinion will be chosen. After confirming the validity of these rules, the researcher applied them to the Malaysian Islamic banking transactions where some of the products were tested on the basis of these rules to see their rulings. Among the products chosen are personal financing, house financing and bank deposits. The result of the application shows that the products are still riddled with suspicions of riba and gharar in their operations.